From Implicit to Explicit CSR in a Scandinavian Context: The Cases of HÅG and Hydro - Carson, Siri Granum (Journal of business ethics, 2015)
The aim of this article is to explain the transition from implicit CSR to explicit CSR that has taken place in Scandinavia over the last two decades. Matten and Moon’s (Academy of Management Review, 33:404–424, 2008) distinction between implicit and explicit CSR is the point of departure for the analysis, which is based on case studies of two Norwegian companies: HÅG and Hydro. On the basis of these case studies, we identify two forces that are pushing the transition from implicit to explicit CSR in Scandinavia: (1) Organizational expressiveness and (2) Re-legitimizing. Both of these measures are adjustments to the globalization of the economy, altering the competitive situation even in highly institutionalized, Scandinavian economies. HÅG, a midsized Norwegian manufacturer of office chairs, made CSR and environmental values an integral part of their expressive strategy in the early 1990s. Hydro, a big Norwegian aluminium producer, made CSR an explicit issue around the turn of the millennium, in an attempt to re-legitimize their business operations in a new market situation where plants in local communities in Norway were shut down and relocated to less regulated regimes in low-cost regions abroad.